1979
DOI: 10.1002/1097-0142(197901)43:1<322::aid-cncr2820430147>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Arterial occlusion of pelvic bone tumors

Abstract: Arterial occlusion of the internal iliac artery was successful in the relief of pain due to primary and secondary neoplasms of the bony pelvis in 8 of 9 patients. These included 3 giant cell tumors, l aneurysmal bone cyst, l recurrent chondrosarcoma, 3 metastatic renal cell carcinoma and 1 metastatic clear cell sarcoma. Calcification of the margin of the lesion occurred in 3 of 4 primary neoplasms after infarction. The transcatheter arterial occlusion was accomplished utilizing Gelfoam and stainless steel coil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 18 publications
1
35
0
1
Order By: Relevance
“…According to this review, a satisfactory decrease of pain was observed in most cases, but duration of pain relief did not exceed 6 months in most cases in the two largest series [14,15], but a longer response was observed by Wallace and Soo in primary tumors [4,8].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…According to this review, a satisfactory decrease of pain was observed in most cases, but duration of pain relief did not exceed 6 months in most cases in the two largest series [14,15], but a longer response was observed by Wallace and Soo in primary tumors [4,8].…”
Section: Discussionmentioning
confidence: 74%
“…However, in some cases where large or predominant involvement of soft tissue or anatomical sites such as the sacrum are seen, this technique cannot be performed [1,2]. Some reports of palliative embolization showed temporary pain relief, but no effective tumoral response [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These report subjective improvement or relief of symptoms ranging from one to 9 months duration [16 Á19]. The majority of these patients were embolized with a combination of gelfoam and metallic coils [16,17,19]. Transcatheter embolization techniques have also successfully been applied to bony metastases from other hypervascular neoplasms such as thyroid [20] and hepatoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical data of all patients are shown comprehensively (please see the Appendix) 9,[21][22][23][24][25][26][27] . For the location of lesions, 41 (93.2%) patients' lesions were detected in the sacrum, while only 4 patients' lesions (1 had GCTB of sacrum and pelvis) were found in the ilium.…”
Section: Description Of Patients' Clinical Featuresmentioning
confidence: 99%